Short-term impacts of wildfire on vegetation recovery, soil chemical properties and community-level physiological profiling in a savanna ecosystem of Botswana - Marenga, Willie; Mapoka, Mpaphidzi; Ultra, Venecio U.; Rantong, Gaolathe; Nduna, Batendi; Tsidu, Gizaw Mengistu (Frontiers in Forests and Global Change, 2025)
IntroductionSavanna ecosystems, an important contributor to Botswana’s economy and occupy up to 86 percent of the land mass of Botswana serving as habitat for wildlife and livestock that are being affected by frequent wildfire which are attributed in part to climate change. While the impact of wildfires on the environment has been extensively studied, there are some uncertainties as to their short-term effects on vegetation dynamics as well as the ability for vegetation to recover from fires. In addition, the impact on soil biogeochemical properties, soil microbial community dynamics, and their interaction within the savanna ecosystem in Botswana, needs to be understood to effectively manage the increasing occurrence of wildfires.Methodology A comparative study was conducted on a burned area and unburned adjacent area within a period after 6 months after wildfire occurrence.Results and discussionOur findings reveal that the ecological impacts of fire on vegetation, soil chemical properties, and microbial community dynamics were not uniform but were strongly mediated by site-specific conditions and the soil type of the associated plant species. Wildfire consistently reduced vegetation cover, plant biomass, and net primary productivity. In contrast, wildfire increased plant species diversity and evenness by disrupting competitive dominance. The impact of wildfire significant increases in soil pH and exchangeable cations (P, K, and Mg) only occurred at the nutrient-rich Mmashoro site and were further localized to the soils under Combretum apiculatum. Conversely, total organic matter increased post-fire at both sites, likely due to ash deposition. The effects of the wildfire on soil microbial community was also site-specific. In Palapye, fire significantly suppressed metabolic activity and functional evenness, leading to a less balanced community but was poorer in key mineral nutrients (K and Mg). Conversely, in Mmashoro, the microbial community associated with the fire-adapted tree C. apiculatum exhibited significant functional resilience, which retained high metabolic activity post-fire. We conclude that certain keystone plant species can mitigate the impacts of fire on belowground processes, creating resilient patches within the landscape. These findings underscore that effective fire management and conservation strategies in savanna ecosystems must be context-specific, accounting for the unique vegetation and soil characteristics of the area.